Wpływ ideologii totalitarnych na konstrukcje prawne stosowane w zakresie ograniczania autonomii woli jednostki na przykładzie modeli wiązania wzorców umownych - Skory, Maciej (Wydawnictwo Uniwersytetu Wrocławskiego, 2021)
The paper aims to examine the influence of totalitarian ideologies on the issue of the mechanism of binding contractual standard forms. Although totalitarian ideologies mainly influence the situation of an individual through the norms of criminal law and administrative law (public law in its broadest sense), private law — especially in its theoretical aspect involving accepted legal constructs — is also influenced by the political doctrines dominant at a given time. As it seems, this also applies to such a technical and far-from-political model as that of contractual binding. It turns out that also in this area totalitarian concepts found room for restricting the scope of individual freedom. This is indicated by a certain correlation between the development of views on the nature of contractual forms and the mechanism of their binding and the intensification or weakening of totalitarian tendencies. Such a conclusion can be derived from the historical analysis of the views represented by the main representatives of French and German doctrine from the mid-19th to the mid-20th century.
Keywords: autonomy of individual will; totalitarian ideologies; mechanism of biding contractual standard forms